E-Commerce Features Influence Purchase Decisions in the Digital Era in Jabodetabek - Rivka Benedicta Vilia; Abdul Rakhman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of Live Streaming, Affiliate Marketing, Free Shipping, and Paylater features on digital consumers' purchase decisions in the Jabodetabek area. The rapid growth of e-commerce, particularly on Shopee and TikTok Shop platforms, has encouraged the utilization of various digital features as marketing strategies. However, previous studies have shown mixed results regarding the effectiveness of these features, indicating the need for further empirical investigation. This research employs a quantitative approach using a survey method involving 215 respondents who are digital consumers of Shopee and TikTok Shop and have made at least three purchases within the last six months. Data analysis was conducted using validity and reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression analysis with SPSS software. The results indicate that Affiliate Marketing and Free Shipping have a positive and significant effect on purchase decisions, with Free Shipping identified as the most dominant factor. Meanwhile, Live Streaming and Paylater do not show a significant effect on purchase decisions. These findings suggest that digital consumers' purchase decisions in the Jabodetabek area are more strongly influenced by creator recommendations and price-related incentives than by interactive features or payment convenience. This study is expected to contribute academically to consumer behavior research and provide practical insights for e-commerce practitioners in designing effective feature strategies.